2005
DOI: 10.3748/wjg.v11.i32.5002
|View full text |Cite
|
Sign up to set email alerts
|

Misperceptions among patients with chronic hepatitis B in Singapore

Abstract: More educational efforts should be focused on patients' misperceptions and target the less educated HBV carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 14 publications
8
37
4
Order By: Relevance
“…34 Some of the previous studies reported that 46.8% of the medical students had understanding on preventive measures such as provision of clean water, improvement in hygiene, restriction to single sex partner, avoidance of transfusion and vaccination (24%, 27%, 6%, 19%, 9%, and 15%), respectively. 50,52 Studies conducted in the general public in India 53 and abroad 54,55 have revealed that the awareness about HBV and Hepatitis B was less. The present study revealed that awareness among the nursing students was better than that among the general public.…”
Section: Discussionmentioning
confidence: 99%
“…34 Some of the previous studies reported that 46.8% of the medical students had understanding on preventive measures such as provision of clean water, improvement in hygiene, restriction to single sex partner, avoidance of transfusion and vaccination (24%, 27%, 6%, 19%, 9%, and 15%), respectively. 50,52 Studies conducted in the general public in India 53 and abroad 54,55 have revealed that the awareness about HBV and Hepatitis B was less. The present study revealed that awareness among the nursing students was better than that among the general public.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient knowledge about the availability of CHB treatment has been reported in other studies, even in the context of good overall knowledge. 16,18 Knowledge about clinical management is critical for people with CHB, given its potential to affect health seeking behaviour; specifically, motivation or willingness to access clinical care. This was demonstrated in an Australian study, where lack of knowledge about antiviral treatment was identified as a major obstacle to accessing healthcare among migrants.…”
Section: Discussionmentioning
confidence: 99%
“…19 Misunderstanding about the transmission of hepatitis B through sharing food and utensils was identified among participants and reflects the findings of other studies. [16][17][18] In a health professionals are a trusted source of information for people with CHB. 16,19 Educating people with CHB was identified by Australian GPs as an important responsibility in their clinical management 20 although systemic barriers have been identified in providing this support, given GPs' busy schedules and workloads, 21,22 and hepatitis B knowledge gaps among some GPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study showed that there were statistical significant differences between education level and knowledge of the patients in which the higher education level has a higher mean knowledge and practice score regarding HBV and HCV. In many studies, better HBV knowledge has been reported to be significantly associated with the educational level Journal of Rare Disorders: Diagnosis & Therapy ISSN 2380-7245 [28,29], persons provided with knowledge and education have been shown to be more likely to practice preventive measures such as vaccination for HBV and screening for HBV and HCV. In conclusion, the present study showed low prevalence of HBsAg and anti-HCV antibody in patient coming for different types of surgical procedures and dental treatment.…”
Section: Discussionmentioning
confidence: 99%